Leadership Character Building through the Final Competition at the Al Hikamussalafiyah Cipulus Purwakarta Islamic Boarding School - Muhammad Said Efendi; Tentri Septiani; Syatiri Ahmad (al-Afkar, Journal For Islamic Studies, 2026)
Education is a crucial issue in human life, from birth to the end of our lives on this earth. Humans were created as the most noble of creatures, as recipients and implementers of teachings. Humans are endowed with the natural instinct to resist evil. However, education has so far been perceived as focusing solely on intellectual potential and paying little attention to emotional or spiritual development. This can result in individuals who are intellectually intelligent but possess poor character, leading to numerous deviant behaviors. This study aims to determine the implementation of leadership character formation at the Al Hikamussalafiyah Cipulus Purwakarta Islamic Boarding School, and to examine the results of leadership character formation through the Musabaqoh Akhirussanah (Education Week) at the Al Hikamussalafiyah Cipulus Purwakarta Islamic Boarding School. This research method uses qualitative research with a descriptive approach to determine and understand the implementation of leadership character formation at the Al Hikamussalafiyah Cipulus Purwakarta Islamic Boarding School. Data collection was conducted through observation and interviews. The research results show that the overall implementation fostered responsible, independent, courageous, disciplined, intelligent, and tolerant character development. The experience gained included additional character development, including religious attitudes, congregational prayer, Dhuha prayer, honesty, tolerance, independence, responsibility, intelligence, and the ability to interact effectively and communicate effectively, all of which contribute to a harmonious atmosphere.